Algunas consideraciones sobre el símil de la línea - Gutiérrez, Raúl (2009)
“Plato grammaticus. On the Platonic Concept of epist?m? in the Theaetetus’ Dream-theory”. Theaetetus’ third definition of epist?m? was traditionally labeled as a precursor of the so-called Justified True Belief Knowledge-Model. Nevertheless, Plato’s point in the last section of this dialogue is more elaborated than this classification deems it. I will examine here why and how Plato develops such a strange doctrine as the Dream-theory in order to offer an interpretation of the problem of justification as discussed in the Theaetetus. Thanks to this strategy, I will show that Plato’s Theaetetus aims to prove that the forms are necessary tools not only to justify true beliefs but also, and consequently, to define what knowledge is. The upshots of this analysis with regard to the complex character of the objects of knowledge will lead to a reconsideration of Plato’s theory of knowledge and metaphysics. Additionally, they will result in a better understanding of his contribution on certain epistemological and semantic issues.